In Vitro Study of the Effects of Five Chemically Modified Tetracycline (CMT) Analogs on Human Epidermal Melanogenesis: Potential as Novel Anti-Melanogenic Agents - Shilpi Goenka; Lorne M. Golub (MDPI AG, 2023)
Treatment of hyperpigmented skin disorders by novel drug candidates without side effects remains an ongoing area of research. Chemically modified tetracyclines (CMTs) are a group of nonantimicrobial tetracycline drugs that have been shown to possess multiple pharmacological activities. We have previously documented the anti-melanogenic effects of CMT-3 and its 9-amino derivative, CMT-308. Herein, we have extended our analysis to evaluate other CMT analogs, namely CMT-1, CMT-4, CMT-5, CMT-6, and CMT-8, for their impact on melanogenesis using primary human epidermal melanocytes (HEMn-DP cells). CMT analogs were screened using a tetrazolium-based assay to identify nontoxic concentration ranges that were further used to analyze the effects of CMTs on cellular melanin content and morphology (via quantitation of dendricity). Cellular tyrosinase (TYR) activity and levels of melanogenesis proteins, TYR, and microphthalmia transcription factor (MITF) were also evaluated to elucidate the mechanisms underlying their effects on melanogenesis. The findings demonstrated that exposure to CMT-8 resulted in notable cytotoxic effects at concentrations >10 µM; hence, all five analogs were further evaluated and compared at 10 µM. None of the five CMT analogs exhibited any impact on intracellular melanin in HEMn-DP cells at the concentration of 10 µM. However, CMT-1, CMT-4, and CMT-8 robustly suppressed dendricity parameters in HEMn-DP cells, while CMT-5 and CMT-6 showed no effect, suggesting that only a subset of CMT analogs can attenuate melanocyte dendricity. Moreover, the analog CMT-5, which has β-diketone blocked, was ineffective, thus confirming the role of this moiety in suppressing dendrite formation. CMT-1 and CMT-8 did not affect cellular tyrosinase activity, while CMT-4 suppressed TYR activity at 10 µM. The capacity of CMT-4 and CMT-8 to suppress dendricity was partly associated with their ability to downregulate MITF protein levels, while CMT-1 had no effect on MITF but suppressed TYR protein levels. The results of this study indicate that CMT-1, CMT-4, and CMT-8 merit further investigation using in vivo studies as potential drug candidates for the treatment of hyperpigmentation disorders.